AVAILABILITY OF INFRASTRUCTURAL FACILITIES FOR THE ESTABLISHMENT OF ENTREPRENEURSHIP CENTRES IN UNIVERSITIES IN SOUTH EAST NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The study investigated the availability of infrastructural facilities for the establishment ofentrepreneurship centres in universities in South East Nigeria. One research question guidedthe study with two hypotheses tested at 0.05 level of significance. Descriptive surveyresearch design was adopted. The population was 116 employees from eight EntrepreneurshipCentres in South East Nigeria. A researcher-developed questionnaire comprising 11 itemsand validated by experts in the field was used to collect data. A pilot test was conducted with theinstrument and the application of the Cronbach Alpha on the data collected yielded coefficient value of 0.76. Mean ratings and standard deviation were used to analyze data inrespect of the research questions while z-test was used to test the null hypotheses. The findingsrevealed that infrastructural facilities needed for the smooth operation of EntrepreneurshipCentres in universities were available in line with the NUC guideline. It was recommendedamong others, that Government and other stakeholders in education should continue toprovide infrastructural facilities and equipment in all entrepreneurship centres. It was alsorecommended that a review of the state of infrastructure and equipment in the centres should becarried out on a regular basis so as to avoid dilapidation and spoilage.
Keywords: Availability, Infrastructural facilities, Entrepreneurship, Study, Centres